PEDAGOGICAL CHALLENGES AND LIMITATIONS OF MOBILE-ASSISTED LANGUAGE LEARNING IN HIGHER EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
The rapid integration of mobile technologies into higher education has significantly influenced language teaching and learning practices. Mobile-Assisted Language Learning (MALL) offers flexibility, learner-centered instruction, and extended learning opportunities beyond traditional classroom settings. Despite its pedagogical potential, the implementation of MALL in higher education is accompanied by a range of challenges and limitations that may hinder its effectiveness. This article aims to critically examine the pedagogical challenges associated with the use of mobile applications in language education at the tertiary level. Drawing on existing international research, the study explores issues related to learner distraction, technological dependency, unequal access to digital resources, limited pedagogical integration, and insufficient teacher preparedness. The findings highlight that while MALL can enhance learner engagement and autonomy, its effectiveness largely depends on informed pedagogical design, institutional support, and teacher guidance. The article concludes that addressing these challenges is essential for the sustainable and effective integration of mobile technologies into higher education language instruction.
Keywords: Mobile-Assisted Language Learning, higher education, pedagogical challenges, mobile applications, language teaching.